Analisis Komponen Fraud Diamond Dalam Mendeteksi Financial Statement Fraud Pada Bank Umum Syariah Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2018 - Farida Nur Fadhilah; Arief Widyananto (LPPM Universitas Islam 45, 2022)
This study aims to examine the components of fraud in the fraud diamond theory in detecting fraud in financial statements. The research variables consist of pressure (financial stability, external pressure and financial target), opportunity (ineffective monitoring), and capability (turnover). directors) that are hypothesized to influence financial statement fraud. The F-Score is used to determine the financial statement fraud. Sampling was selected using a purposive sampling method, namely Islamic banks that have gone public or are listed on the Indonesia Stock Exchange (IDX) in the period 2014 to 2018. The data analysis method uses multiple regression using SPSS 16 software. Based on the results of hypothesis testing using the t test, it is obtained that financial stability (ACHANGE) and ineffective monitoring (BDOUT) variables have a significant positive effect on financial statement fraud. Meanwhile, external pressure (LEV) has a significant negative effect on financial statement fraud. And financial target (ROA) and capability (DCHANGE) have no significant effect on financial statement fraud. Tests using the F (simultaneous) test found that the variables of financial stability, external pressure, financial target, ineffective monitoring and capability together have an influence on financial statement fraud.